Information level of dental students and dental surgeons on prescription in a city of Paraiba state, Brazil (Research, Society and Development, 2020)
Objective: To analyze the knowledge and the self-confidence of dental surgeons and Dentistry students from the Paraiba State University (UEPB), regarding to the ethical, legal and pharmacological aspects of an accurate prescription in clinical practice. Methods: The sample (N=56) was valuated through the application of a questionnaire divided into three blocks that included the perception of the discipline of Drug Therapy or Pharmacology, current legislation and rules about prescription and the drug indication itself. Data was analyzed in a descriptive way and the multivariate logistic regression. Results: 89.3% of the research participants said that the duration of discipline of Drug Therapy or Pharmacology was not enough to make them fell self-confident to prescribe; 53.6% of them do not believe the discipline was taught at the right moment over the graduation. Between groups, only 6.6% of the Dentistry students recognized the oral hypoglycemic agents as the only drug that cannot be prescribed by the dentist, while 30% of the dental surgeons said the same (p=0,040), indicating that these ones have 6.9 times more chance to hit the right answer than the first ones (IC 95%: 0.023 – 0.915). A hypothetical situation of an older patient alcoholic consumer and with liver disease in need of painkiller and the fact of paracetamol is contraindicated was suggested: 69.5% of the Dentistry students said that this drug can be prescribed, while only 20% of the dentists said so (p=0.009), denoting that these ones have 9.43 times more chance to hit the right answer than the first ones (IC 95%: 0.020 – 0.573). Conclusions: The dental surgeons had a highest hit percentage than the Dentistry students. It is suggested that is necessary to re-evaluate the teaching of the subject.